Ответ:
х = 7
Объяснение:
2(3х-11) - (3-5х) = 4(х+6)
6х - 22 - (3-5х) = 4(х+6)
6х - 22 - 3 + 5х = 4(х+6)
6х - 22 - 3 + 5х = 4 + 24
11х - 22 - 3 = 4х + 24
11х - 25 = 4х + 24
11х - 25 - 4х = 24
11х - 4х = 25 + 24
7х = 24 + 25
7х = 49
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
х = 7
Объяснение:
2(3х-11) - (3-5х) = 4(х+6)
6х - 22 - (3-5х) = 4(х+6)
6х - 22 - 3 + 5х = 4(х+6)
6х - 22 - 3 + 5х = 4 + 24
11х - 22 - 3 = 4х + 24
11х - 25 = 4х + 24
11х - 25 - 4х = 24
11х - 4х = 25 + 24
7х = 24 + 25
7х = 49
х = 7